Biyaheng Pinoy a Mindanao travelogue - Alegre, Edilberto N.; Bughaw (Firm) (Quezon City Bughaw, 2020)
Author's account traveling to Mindanao, Philippines.
Keywords: Alegre, Edilberto N. -- Travel -- Philippines -- Mindanao Island; Philippine essays (English).; Mindanao Island (Philippines) -- Description and travel